KOMUNIKASI MEDIA SOSIAL DAN NILAI-NILAI BUDAYA PANCASILA SOCIAL MEDIA COMMUNICATIONS AND CULTURAL VALUES of PANCASILA - Luh Suryatni (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2018)
The third wave in human civilization according to Alvin Toffler is information technology which accelerates the communication process and interaction to convey information in social media. Medium of communication with the Internet network resulted in a socio-cultural changes which can be positive or negative. Positive changes can facilitate intercultural communication, exchange of knowledge, and simplify business transactions. Meanwhile, the negative changes will have a cultural shock as the impact because of the information which was obtained from social media is taken for granted, believed to be true and applied in everyday life even though it is not in accordance with the surrounding culture. This can lead to changes in values, norms, and rules of communication. In connection with social media, it is regulated in Law No. 11 Year 2008 on Electronic Transaction Information (ITE) as a social control in conveying information based on Constitution of the Republic of Indonesia 1945 (UUD NRI 1945) article 28, which can reflect the cultural values of Pancasila.